THE CORELATION BETWEEN HEALTH BEHAVIOR WITH PERCEPTION SOCIETY TOWARDS TUBERCULOSIS CLIENT BASED ON HEALTH PROMOTION MODEL - Veby Fransisca Rozi; Devi Cynthia Dewi (Proceeding B-ICON, 2023)
Introduction: Tuberculosis (TB) is a chronic infection that usually affects the lungs caused by Mycobacterium tuberculosis. This bacterium is transmitted by droplet nuclei, airborne droplets produced when an infected person coughs, sneezes, talks or sings. In Province Bengkulu at 2015 there were 3,410 cases of people affected by Tuberculosis. Sawah Lebar region was found 62.352 % exposed to Tuberculosis cases. Knowledge and information about Tuberculosis purpose to reduce the spread of disease. A good perception of good health behavior among people is very important to reduce tuberculosis. This research aims to identifiy the corelation between perceptions with public health behavior toward Tuberculosis patient based on health promotion model in working area of Sawah Lebar Puskesmas Bengkulu.Method:. Respondents are the community living around Sawah Lebar Puskesmas Bengkulu. With a total of 90 respondents. Data were obtained by distributing questionnaires. This research was using Kolmogorof-smirnov normality test, if the test result is abnormal then the researcher use spearmen's rho with significance level ? <0,05.Result: Perceived benefit, perceived barrier, interpersonal influence and situational influence has positive correlation with health behavior ( p= 0,001 r= 0,478; p=0,005 r= 0,387; p= 0,001 r= 0,357; p= 0,001 r= 0,347). The higher perceived benefit, perceived barrier, interpersonal influence and situational influence then health behavior will also be better.Discusion: Nurse and other health staff can implement program that can increase the reach of information and community knowledg about Tuberculosis. Information and education about Tuberculosis in Sawah Lebar Bengkulu can keep the situation around their residence area free from spreading Tuberculosis disease.Keywords: Tuberculosis, Health Promotion Model